Rising trend of E-Commerce purchase by Indian Youths - Agrawal, Aditi (IJRDO - Journal of Business Management, 2015)
As technology continues to grow rapidly, E-Commerce players are adapting newer techniques to facilitate efficient online selling and buying. More recently, with the introduction of flash sales and daily deals from various companies, E-Commerce has brought forward technnovation to the retail sector. Especially in developing countries like India, E-Commerce is on boom. Many big players are ready to invest in E-Commerce and are earning huge revenues. The major reason for growth of ECommerce in India is the astronomical population and youth. Youth possess a vital role in the growth of E-Commerce. The growth is driven by rapid technology adaptation led by the increasing use of devices such as smartphones and tablets and access to the internet through broadband 3G etc, which led to an increased online consumer base.